PENDAMPINGAN MANAJEMEN AGRIBISNIS SAYUR SEMI KIMIA DI DESA PULOSARI - Ebrilyani, Elok; Sundahri, Sundahri; Munandar, Denna Eriani; Fariroh, Indri; Harsanti, Restiani Sih (PAPUMA: Journal of Community Services, 2023)
Pulosari is one of the villages that is the place for the implementation of the Community Service Program Back to Village 2020 Universitas Jember. The main target of the Community service program is Gibrellyn L. Stea who is a member of the InsyaAllah Tani organization. This organization is engaged in semi-organic vegetable cultivation. The problem faced by target in the business being carried out is the lack of management applied, which causes profit opportunities to decrease and even loss. This problem became the basis for select topic in this community service program, application of agribusiness management in semi-organic vegetable farming in Pulosari Village. The purpose of this program is that business actors can apply agribusiness management properly so that no profit opportunities are wasted and can improve business management methods to make them better and more organized. This program had been taken on 1st of July until 14th of August 2020. The method used to achieve the objectives in this program is structured in several programs including the socialization of the application of agribusiness management and the direct application of management to semi-organic vegetable farming. The result of this community service is that the target is to better understand the importance of management and know how to better manage the business, thus the opportunity for benefits to be obtained in the future will be greater.